Phylogenetic relationships of some Scenedesmus strains (Chlorophyta) isolated from the hoankiem lake by basing on ITS-1 DNA sequences - bach, Nguyen Duc; Hong, Dang Diem; Tien, Duong Duc; Dong, Nguyen Van (Academia Journal of Biology, 2015)
Six strains of Scenedesmus, differing in their organic body scale morphology, were isolated from the Hoankiem lake, Hanoi city. Using PCR technique, we amplified and sequenced the ITS-1 (internal transcribed spacer), located in the region of DNA encoding for 18S and 5,8 S ribosomes. Based on the alignment of the ITS-1 sequence and the phylogenetic representation, six strains were divided into two main clusters (genetic distant coefficient was 0.34179). One of which was absolutely identical in genetic-homology and composed of S. obliquus (Turp.) var. alternans, S. obliquus (Turp.) Kuetz. var obliquu 367, S. obliquus (Turp.) var. sp. and Scenedesmus quadricauda var. sp; these four strains were suggested to be an exclusive species of the genus Scenedesmus. The second group included Scenedesmus quadricauda (Turp.) var. abudans Kirchn and Scenedesmus ellipsoides Chod (genetic distant coefficient was 0.00136) might be two distinct species but were almost identical in genetic relationship.